Immigrant entrepreneurship in Europe: a comparative empirical approach - Riccardo Rinaldi; Alessandro Arrighetti; Andrea Lasagni; Jacopo Canello (ZBW - Leibniz Information Centre for Economics, 2023)
The aim of this paper is to use a multi-country approach to assess the role played by individual characteristics and local labor market conditions in influencing migrants' self-employment decisions. The empirical investigation exploits data from the EU Labor Force Survey for the 2005-2016 period and focuses on two countries (Italy and the UK) characterized by significantly different labor market dynamics. Our findings suggest that the impact of individual characteristics is similar across countries, whereas the role of the local economic environment changes significantly, resulting in different migrant entrepreneurship patterns. These findings appear to be consistent with the most recent strand of literature, suggesting that while individual characteristics of self-employed migrants are similar across countries, national and regional differences play a key role in determining migrants' entrepreneurial propensity.
Keywords: 330; migrant; entrepreneurship; regional economics